Solution-Based Micro- and Nanoscale Metal Oxide Structures Formed by Direct Patterning for Electro-Optical Applications - Yeh, Chun-Cheng (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.